The algorithmic dance: YouTube's Adpocalypse and the gatekeeping of cultural content on digital platforms - Sangeet Kumar (Internet Policy Review, 2019)
The March 2017 advertiser revolt on YouTube, popularly known as the adpocalypse, introduced widespread and radical changes on the platform's policies related to the moderation of content, their 'monetisability' and the terms of the relationship between creators and the platform. These changes in turn have caused significant discontent within the creator community while also gradually transforming the predominant nature of content on the platform. This essay analyses this controversy that is yet to be subjected to a scholarly investigation, in order to probe the ways in which algorithmic moderation of content affects their monetisability and consequently the viewership patterns of culture. Through closely studying the new regime of content moderation and analysing user testimonies in the aftermath of the 'Adpocalypse', this essay poses critical questions about the public utility like role of digital platforms whose gatekeeping function remains largely outside the purview of public debate and deliberation.
Keywords: 300; Algorithms; Gatekeeping; Platforms; YouTube; Monetisation; Adpocalypse